Management of cross-functional processes in culture institution - E. G. Khodzhayan (Омский научный вестник: Серия "Общество. История. Современность")
The article substantiates approach to process-based management as a key factor of market stability of culture institution. The basic principles of process-based management of culture institution such as allocation and description of crossfunctional processes, customer orientation, head leadership, interaction between workers of arts, administrative and management functions, continuous improvement, processes measurable, relationships with stakeholders, system approach, synergy are formulated. Theoretical aspects of management of cross-functional processes are considered. Classification of cross-functional business-processes of culture institutions is given